Orientasi Sumber Daya Manusia Dalam Meningkatkan Kompetensi Profesionalisme Guru - Merlya Kusuma; Binti Maunah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The purpose of this article is to explain the orientation of human resources in improving the competence of teacher professionalism. This method uses library research. Data were obtained from various sources, namely: books, journals, articles, and book chapters. In the early stages, the authors collected data from various sources which were then compiled in the form of texts ready to be discussed in class discussions, the results of the discussions and the existence of various inputs, the manuscripts were then revised and discussed in subsequent discussions. The final results of the discussion are then ready to be published on a wider scale. The focus of the discussion in this article is: 1) human resource orientation, 2) stages of human resource orientation, 3) teacher professional competence, 4) human resource management in improving teacher professionalism.